Spermatogonia, Germline Cells, and Testicular Organization in the Characiform Prochilodus lineatus Studied Using Histological, Stereological, and Morphometric Approaches - De Melo Dias, Gisele Cristiane; Cassel, Monica; Oliveira De Jesus, Lazaro Wender; Batlouni, Sergio Ricardo [UNESP]; Borella, Maria Ines (Wiley-Blackwell, 2017)
Prochilodus lineatus is an important representative of the order Characiformes and a species that offers great advantages to fish farming. Therefore, detailed knowledge of its reproductive biology can be applied to various fields of production and biotechnology. In this study, we have identified testicular germ cells during spermatogenesis and have evaluated the volumetric proportion of the testes occupied by structures of the tubular and intertubular compartments. In addition, the individual volume of type A spermatogonia was measured and used to estimate the mean number of these cells per testis. Gonads of adult P. lineatus males were extracted and fixed. Light and transmission electron microscopy were applied to fragments of three testicular regions. Histological, stereological, and morphometric analyses were performed. The stereological data suggest that components of the tubular and intertubular compartments of the P. lineatus testes present a uniform distribution in all three regions and therefore reflect regions with similar distributions of cell types. In addition, P. lineatus testes showed similar to 0.6% of type A spermatogonia, as well as a predominance of cysts of primary spermatocytes and spermatids during the reproductive phase evaluated. The results from this study provide a better understanding of the morphology and structure of the testis and of the characterization of the type A spermatogonia in P. lineatus. The nuclear diameter of germ cells also decreases significantly during spermatogenesis. The data presented herein are the first of its kind for the order Characiformes and may be useful for future biotechnology studies on fish reproduction. (C) 2016 Wiley Periodicals, Inc.
Keywords: germ cells; type A spermatogonia; morphometry; stereology; fish adult testes